UNDERSTANDING ACCOUNTING AND SHARIA VIEWS ON BITCOIN CRYPTOCURRENCY AS A DIGITAL-BASED FINANCIAL INSTRUMENT - Sabana, Mochamad Arief; Nurfahmiyati; Amaliya, Ima (UPT Publikasi Ilmiah UNISBA, 2024)
In Indonesia, cryptocurrency began to develop, and Indonesian traders started to use it widely. This is a phenomenon, given the need for cryptocurrency accounting processing. This research seeks to examine and test cryptocurrency and blockchain technology with the approach and supervision of the Indonesian PSAK and focuses on the accounting treatment of cryptocurrencies in Indonesia. It also seeks to understand the way Sharia Maqasid perceives transactions using cryptocurrency and blockchain. The purpose of this study is to conduct a study of cryptocurrency accounting based on PSAK applied in Indonesia and examine the views of Sharia Maqasid. This study uses a literature review model to define cryptographic accounting and literature on the Maqasid view of sharia. The results show there is no accounting treatment for cryptocurrency transactions, regardless of whether the transaction is treated as cash, assets, or inventory. Furthermore, the view of the Islamic Maqasid on this transaction is permissible. Keywords : Cryptocurrency, Understanding Accounting, Bitcoin, Digital Currency.